Vistos de dentro: os ODS a partir de um estudo de caso de um departamento financeiro da administração pública - Cardeira, Paulo (2021)
The main objective of this work is to understand the extent to which Public Administration workers are aware of and contribute to the implementation of the Sustainable Development Goals (SDGs) in their work space. In methodological terms, the research is based on a qualitative approach through semi-structured interviews with 10 civil servants from a department in the financial area of Public Administration in Portugal. The results show that, in the case of the analyzed department, there is already an awareness and commitment of public servants with the SDGs within the scope of their functions, having identified trade-offs that privilege environmental criteria over economic ones. The research contributes with a set of suggestions presented by the employees interviewed in order to deepen their commitment to environmental sustainability and the implementation of the SDGs in Public Administration.